The Influence of Foreign Ownership, Company Size, Profitability, and Sales Growth on Transfer pricing (Study on Manufacturing Companies on the IDX 2021-2024) - Putri, Lendy Syahira Lismawati; Widiawati, Hestin Sri; Winarko, Sigit Puji (STIE Tri Bhakti, 2025)
This research is motivated by the development of globalization and the increasing of foreign direct investment in Indonesia, which encourages multinational companies to implement more complex cross-entity business strategies. The strategy used is transfer pricing, which is the pricing of transactions of goods, services, or intangible assets between entities within a corporate group. Transfer pricing is used to support operational efficiency, evaluation of business unit performance, and allocation of costs and revenues. This study aims to analyze the influence of foreign ownership, company size, profitability, and sales growth on transfer pricing in manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the period 2021–2024. This study employs a quantitative approach using multiple linear regression analysis techniques analyzed with SPSS 30 software. The data used is secondary data obtained from the company's annual financial reports. The sampling technique used is purposive sampling, resulting in 52 company data as samples. The research results indicate that partially, company size, profitability, and sales growth have a significant effect on transfer pricing, while foreign ownership does not show a significant effect. Simultaneously, foreign ownership, company size, profitability, and sales growth significantly affect transfer pricing. The findings of this study indicate that companies with large scale, high profitability, and continuously growing sales tend to be more active in implementing transfer pricing strategies for managing financial performance among entities within the group.